The Intention of Accounting Students in Pursuing Professional Qualification - Mohamed Saat, Maisarah; Azizah Ismail, Annur; Mohd. Jamal, Noriza; Idris, Norhalimah; Ramakrishnan, S (International Journal of Engineering and Technology, 2018)
Malaysia still has a long journey to reach its mission that is to have 60,000 qualified accountants by year 2020. This scenario has motivated this study in examining the accounting students’ intention to pursue accounting professional qualification. It also attempted to identify the differences in their demographic background and their intention in attaining such qualification. A total of 130 accounting students from a public university in Malaysia participated in this study and the modified survey questionnaire was distributed among them. The findings revealed that almost half of respondents were certain while the other half probably will pursue their professional qualification. ACCA, CIMA and ICAEW are top choices of professional qualifications. In general, the accounting students have good perceptions on the credibility of accounting profession. It is recommended that the educators and the professional bodies play their roles to encourage and motivate accounting students to pursue their professional qualification. Â Â